(untitled) (Research, Society and Development, 2021)
The health of workers is extremely important for the elaboration of their activities in the company, still dealing with environments that can contribute to the ergonomic risks in routine office activities. To this end, this research aimed to assess the ergonomic risks of the company ACS Empresarial, located in the municipality of Itabira / MG. In addition to surveys of ergonomic risks, an interview was conducted with company employees to verify whether physical objects for the routine performance of work, such as chairs, tables, computers, lighting that may cause discomfort during the work routine. In addition to physical objects, the interview aimed to identify signs of cognitive ergonomics, asking questions regarding occupational stress. With the results obtained by the interviews, the ergonomic factors that affect the work routine according to the employees were analyzed and proposed improvements for the prevention of future ergonomic work accidents that could occur.